Diseño de una máquina compactadora de ladrillos automática con sistema de mando y moldes intercambiables (2025)
The present thesis aims at the development of an automatic brick compactor machine with a control system and 3 different interchangeable molds for the Faculty of Architecture of the University of America, so that students can carry out practical tests of the manufacturing process of standard and quality bricks, the development of this machine will start from the detailed design appropriate to this need, for this we will incorporate three systems; on the one hand, we have the mechanical system or drive assembly that will transmit the movement, convert potential energy into mechanical energy and support the system comprised of the hydraulic body, loads, joints and components, in relation to the previous one, the second integrated system will consist of a hydraulic circuit controlled by automatic control, which will give in the first place, the feeding of the raw material and will allow the block elevators to return to their initial position, then will proceed its compaction and restoration of the load, taking into account its mechanical limit switch and finally will carry out the extraction and placement of the block. At the same time, the third system that we will integrate will be linked to the mechanical part since we will integrate three different types of interchangeable molds of different sizes.